Responses of coastal fishery resources to rapid environmental changes - Peltonen, Heikki; Weigel, Benjamin (Wiley, 2022)
Coastal systems experience strong impacts of ongoing environmental change, affect-ing fish communities and subsequently fishery yields. In the Baltic Sea, the combined effects of climate-induced changes and eutrophication-related pressures constitute major threats to its living resources. Although much work has been devoted to unco-vering environmental impacts on the commercially most valuable fish stocks, only lit-tle is known about community-wide responses of fished species and howenvironmental change may affect their yield. In this study, the authors use a jointspecies distribution modelling framework to disentangle environmental impacts onspecies-specific fishery yields of 16 fished species along the coast of Finland overfour decades. The authors show that environmental covariates substantially contrib-uted to variations in fishery yields and are likely to have strong impacts on fishedresources also in the future. Salinity and near-bottom oxygen concentration emergedas the strongest environmental drivers of yields at the community level, whereastemperature was particularly important for cod (Gadus morhua) and sprat (Sprattussprattus) yields. The authors found shore density to be an important predictor forfisheries resources especially for freshwater fish. The results of this study suggestthat the changes in environmental conditions during the past four decades had a pos-itive effect on the yields of freshwater and warm-affinity species, whereas yields ofmarine cold-affinity species have been mainly negatively affected by contractingfavourable habitats, becoming warmer and less saline.